Small round cell sarcoma tumoroid biobank reveals CIC::DUX4 sarcoma vulnerability to MCL-1 inhibition - Femke C. A. S. Ringnalda; Gijs J. F. van Son; Laurens H. G. Verweij; Seok-Young Kim; Vicky Amo-Addae; Uta E. Flucke; Laura S. Hiemcke–Jiwa; Karin P. S. Langenberg; Jos A. M. Bramer; Lotte Heimans; Michiel A. J. van de Sande; Winan J. van Houdt; et al. (Nature Communications)
Abstract Small round cell sarcomas (SRCS) are highly aggressive tumors in soft tissues and bone of mostly children and young adults. Despite being different in many aspects, including genetics, possible cell-of-origin, and pathology, patients with any of these entities all receive the same therapeutic regimen. Although several pre-clinical models of Ewing sarcoma have been established, such as cell lines and patient-derived tumor xenografts, few models exist for other SRCS. Here, we describe a pediatric SRCS tumor organoid (tumoroid) biobank containing long-term tumoroid cultures with different translocations, including EWSR1::FLI1, EWSR1::ERG, CIC::DUX4, and BCOR-rearrangements. Using histology, whole genome sequencing and RNA sequencing, we demonstrate that these tumoroids retain histological characteristics, known marker gene expression and chromosomal rearangements of their matching patient tumors. In addition, we compare mutation clusters in the tumoroids across patient-matched longitudinal samples, which shows that cellular heterogeneity is maintained. Drug screening on the tumoroid models unveils entity-specific drug sensitivity to various cytotoxic compounds and targeted compounds, including MCL-1 inhibitors for CIC::DUX4 sarcomas. Taken together, this newly established SRCS patient-derived tumoroid biobank represents a promising source of material for future basic cancer research and drug screening.